Constitutional Protection of The right to education in Iraq - Sulaiman, Assistant teacher: Eman Hamooud (The college of law and political science journal, 2024)
Constitutional protection is one of the lofty goals that societies pursue to ensure that its members enjoy equal rights and freedoms. Therefore, this research reviewed the most important constitutional principles which apply to guarantee the right to education. In accordance with the Constitution of the Republic of Iraq of 2005, there are the principle of the rule of law and the principle of equal opportunities. In addition to explaining the texts of the various Iraqi legislations related to the field of research ، Through analysis of legislative texts ، highlighting its weaknesses and strengths. The research concluded that education is a basic human right. As we as, the main factor in ensuring and knowing his rights. It also concluded with several proposals، the most important of which is: Repeal any legislative provisions or administrative instructions that involve any discrimination in education، In addition، the difference in treatment between citizens is based on need or merit With regard to school fees or granting scholarships، Or by issuing licenses and providing the necessary facilities to pursue study abroad.